The Effect of E-Recruitment And E-Selection on Interest in Applying For Jobs at the Central Statistics Agency of Lamongan Regency in the 2024 Statistics Partner Program (Case study of generation Z of Lamongan regency) - Iffah Robiatul Muflika; Nurul Badriyah; Titin Titin (Sean Institute, 2025)
This study aims to determine promotion, price perception, and product diversity, to partial, simultaneous, and most dominant purchase decisions. The research method used is causal associative with a quantitative approach. The results of the study showed that promotion did not have a significant effect. Meanwhile, price perception, and product diversity have a positive and significant effect on purchasing decisions. Promotions, price perceptions, and product diversity simultaneously have a positive and significant effect on purchasing decisions. The price perception variable has the most dominant influence.